Human papillomavirus 16 (HPV16) and HPV52 E6‐specific immunity in HIV‐infected adults on combination antiretroviral therapy. Issue 5 (20th September 2016) - Leng, CY; Low, HC; Chua, LL; Chong, ML; Sulaiman, H; Azwa, I; Roberts, JM; Kamarulzaman, A; Rajasuriar, R; Woo, YL
Abstract : Objectives: Human papillomavirus (HPV)‐associated cancers disproportionately affect those infected with HIV despite effective combination antiretroviral therapy (cART). The primary aim of this study was to quantify HPV16 and HPV52 E6‐specific interferon (IFN)‐ γ enzyme‐linked immunospot (ELISPOT) T‐cell responses, a correlate of protective immunity, in the first year following cART initiation and subsequently in those patients with suboptimal (sIR) and optimal (oIR) immune reconstitution. Methods: Ninety‐four HIV‐infected patients were recruited to the study; a longitudinal cohort of patients recruited just prior to commencing cART and followed up for 48 weeks ( n = 27), and a cross‐sectional cohort ( n = 67) consisting of patients with sIR (CD4 T‐cell count < 350 cells/ μ L) and oIR (CD4 T‐cell count > 500 cells/ μ L) after a minimum of 2 years on cART. Controls ( n = 29) consisted of HIV‐negative individuals. IFN‐ γ ELISPOT responses against HPV16 and HPV52 E6 were correlated to clinical characteristics, anal and oral HPV carriage, T‐cell maturational subsets, markers of activation, senescence and T‐regulatory cells. Results: HPV16 and HPV52 E6‐specific T‐cell responses were detected in only one of 27 patients (3.7%) during the initial phase of immune recovery. After at least 2 years of cART, those who achieved oIR had significantly higher E6‐specific responses (9 of 34; 26.5%) compared with those with sIR (2 of 32; 6.3%) ( P = 0.029). Apart from higher CD4 T‐cell counts and lower CD4 T‐cell activation, no other immunological correlates were associated with the detection of HPV16 and HPV52 E6‐specific responses. Conclusions: HPV16 and HPV52 E6‐specific IFN‐ γ T‐cell responses, a correlate of protective immunity, were detected more frequently among HIV‐infected patients who achieved optimal immune recovery on cART (26.5%) compared with those with suboptimal recovery (6.3%).